Numerical Investigation on the Effect of the Diversion Layer on the Flow Field of the α-Type Cyclone Separator. Issue 1 (1st August 2022) - Fan, J L; Li, W H; Zhang, P; Chen, G H
Abstract: The flow field stability and separation performance of the cyclone separator decrease significantly as its size increases. An inner guider was added in α -type cyclone separator, and in this paper, a numerical investigation on the gas-solid two-phase flow in the α -type cyclone was conducted. The Reynolds stress model and the DPM model were used to simulate the gas flow and the motion of particles, respectively. The influence of the guider on the velocity field, pressure field, turbulent kinetic energy field, and particle separation efficiency of the cyclone separator was analyzed. The results showed that after adding an inner guider, the tangential velocity increases, the turbulent kinetic energy decreases, the downward area of the axial airflow increases, and the number of airflow-carrying particles downward increases.